Sosialisasi Peran Informatika Medis dalam Dunia Teknologi dan Kesehatan pada Siswa SMK Sulthan Muazzam Syah Pekanbaru - Andi Cahyono; Ervira Dwiaprini As Syifa; Tarbiah Nurjanah; Dwi Indah Purnama; Sri Utami Rizta (Fakultas Teknik Universitas Cenderawasih, 2024)
The community service titled Socialization of the Role of Medical Informatics in Technology and Healthcare for Students of SMK Sulthan Muazzam Syah Pekanbaru aims to enhance students' understanding of the importance of information technology in the medical field. This activity was held on campus, focusing on the application of information technology in improving the efficiency, accuracy, and speed of healthcare services. The socialization involved 30 students who actively participated through interactive presentations and simulations of medical technology use cases. The methods used included visual presentations and open discussions about the role of technology in medical diagnosis and data management. Students were also given the opportunity to ask questions regarding career opportunities in the field of medical informatics. The results showed an increased understanding among students about the role of information technology in healthcare, with positive responses concerning career prospects in this field. This activity is expected to motivate students to explore further the application of information technology in the healthcare sector. Future activities are recommended to include more in-depth workshops or technical training in medical informatics.